STAT3 decoy oligonucleotide-carrying microbubbles with pulsed ultrasound for enhanced therapeutic effect in head and neck tumors. - Thiruganesh Ramasamy (Public Library of Science (PLoS), 2020)
Signal transducer and activator of transcription-3 (STAT3) is an oncogenic transcription factor implicated in carcinogenesis, tumor progression, and drug resistance in head and neck squamous cell carcinoma (HNSCC). A decoy oligonucleotide targeting STAT3 offers a promising anti-tumor strategy, but achieving targeted tumor delivery of the decoy with systemic administration poses a significant challenge. We previously showed the potential for STAT3 decoy-loaded microbubbles, in conjunction with ultrasound targeted microbubble cavitation (UTMC), to decrease tumor growth in murine squamous cell carcinoma. As a next step towards clinical translation, we sought to determine the anti-tumor efficacy of our STAT3 decoy delivery platform against human HNSCC and the effect of higher STAT3 decoy microbubble loading on tumor cell inhibition. STAT3 decoy was loaded on cationic lipid microbubbles (STAT3-MB) or loaded on liposome-conjugated lipid microbubbles to form STAT3-loaded liposome-microbubble complexes (STAT3-LPX). UTMC treatment efficacy with these two formulations was evaluated in vitro using viability and apoptosis assays in CAL33 (human HNSCC) cells. Anti-cancer efficacy in vivo was performed in a CAL33 tumor murine xenograft model. UTMC with STAT3-MB caused significantly lower CAL33 cell viability compared to UTMC with STAT3-LPX (56.8±8.4% vs 84.5±8.8%, respectively, p<0.05). In vivo, UTMC with STAT3-MB had strong anti-tumor effects, with significantly less tumor burden and greater survival compared to that of UTMC with microbubbles loaded with a mutant control decoy and untreated control groups (p<0.05). UTMC with STAT3 decoy-loaded microbubbles significantly decreases human HNSSC tumor progression. These data set the stage for clinical translation of our microbubble platform as an imaged-guided, targeted delivery strategy for STAT3 decoy, or other nucleotide-based therapeutics, in human cancer treatment.